Secure P2P Data Storage and Maintenance - Nouha Oualha; Melek Önen; Yves Roudier (International Journal of Digital Multimedia Broadcasting)
P2P data storage requires strong reliability and security assurances. Existing data storage solutions have been designed for centralized as well as distributed settings; yet they do not address the security and cooperation issues raised by self-organization. P2P systems also introduce new needs regarding data availability due to the dynamicity of the infrastructure, which are unaddressed so far. This paper first discusses the approaches for tackling these problems. A solution is then introduced that relies on self-organizing security mechanisms in conjunction with a data rejuvenation scheme using erasure codes.